Serum PSA and cure perspective for prostate cancer in males with nonpalpable tumor - Dall'Oglio, Marcos Francisco [UNIFESP] (2005)
INTRODUCTION: Many studies have shown the association between PSA levels and the subsequent detection of prostate cancer. In the present trial, we have studied the relationship between preoperative PSA levels and clinical outcome following radical prostatectomy in men with clinical stage T1c. MATERIALS AND METHODS: 257 individuals with clinical stage T1c undergoing retropubic radical prostatectomy were selected in the period from 1991 to 2000. Following surgery, biochemical recurrence-free survival curves were constructed according to PSA levels between 0-4; 4.1-10; 10.1-20 and > 20 ng/mL. RESULTS: Of the total of 257 selected patients, 206 (80%) had Gleason scores from 2 to 6 and 51 (20%), presented Gleason scores 7 and 8, as defined by the pathological report from prostate biopsy. There was no biochemical recurrence of disease when the PSA was lower than 4, regardless of Gleason score. Biochemical recurrence-free survival according to PSA between 0-4; 4.1-10; 10.1-20 and > 20 was 100%, 87.6%, 79% and 68.8% for Gleason scores 2-6 and 100%; 79.4%; 40% and 100% for Gleason scores 7-8 respectively. When all individuals were grouped, regardless of their Gleason scores, the probability of biochemical recurrence-free survival was 100%, 65.1%, 53.4% and 72.2% according to PSA between 0-4; 4.1-10; 10.1-20 and > 20 ng/mL respectively. CONCLUSION: Non-palpable prostate cancer presents higher chances of cure when the PSA is inferior to 4 ng/mL.